Management : tasks, responsibilities, practices - Drucker, Peter F. (New York : Harper & Row, 1974)
The emergence of management in this century may have been a pivotal event of history. It signaled a major transformation of society into a pluralist society of institutions, of which managements are the effective organs. Management, after more than a century of development as a practice and as a discipline, burst into public consciousness in the management boom that began after World War II and lasted through the 1960s. What has the boom accomplished? What have we learned? And what are the new knowledges we need, the new challenges we face, the new tasks ahead, now that the management boom is over?
The alternative to tyranny -- The emergence of management -- The management boom and its lessons -- The new challenges -- The dimensions of management -- Managing a business : the Sears story -- What is a business? -- Business purpose and business mission -- The power and purpose of objectives : the Marks & Spencer story and its lessons -- Strategies, objectives, priorities, and work assignments -- Strategic planning : the entrepreneurial skill -- The multi-institutional society -- Why service institutions do not perform -- The exceptions and their lessons -- Managing service institutions for performance -- The new realities -- What we know (and don't know) about work, working, and worker -- Making work productive : work and process -- Making work productive : controls and tools -- Worker and working : theories and reality -- Success stories : Japan, Zeiss, IBM -- The responsible worker -- Employment, incomes, and benefits -- "People are our greatest asset." Management and the quality of life -- Social impacts and social problems -- The limits of social responsibility -- Business and government -- Primum non nocere : the ethics of responsibility -- Why managers? -- What makes a manager? -- The manager and his work -- Design and content of managerial jobs -- Developing management and managers -- Management by objectives and self-control -- From middle management to knowledge organization -- The spirit of performance -- The effective decision -- Managerial communications -- Controls, control, and management -- The manager and the management sciences -- New needs and new approaches -- The building blocks of organization And how they join together -- Design logics and design specifications -- Work- and task-focused design : functional structure and team -- Result-focused design : federal and simulated decentralization -- Relations-focused design : the systems structure -- Organization conclusions. Georg Siemens and the Deutsche bank -- Top-management tasks -- Top-management structure -- Needed : an effective board -- On being the right size -- Managing the small, the fair-sized, the big business -- On being the wrong size -- The pressures for diversity -- Building unity out of diversity -- Managing diversity -- The multinational corporation -- Managing growth -- The innovative organization -- Conclusion : the legitimacy of management.
Includes bibliographical references and index.
Keywords: MANAGEMENT